Lichenized fungi of the chestnut grove in Livari (Rumija, Montenegro) - Mayrhofer, Helmut; Drescher, Anton; Steševic, Danijela; Bilovitz, Peter Othmar (Acta Botanica Croatica, 2013)
Sixty taxa (59 species and 1 variety) of lichenized fungi are reported from a chestnut grove in Livari. The majority of them (55 species and 1 variety) occurred on Castanea sativa. The recently described Xylographa soralifera is new to the Balkan Peninsula.The lichenicolous fungus Monodictys epilepraria growing on Lepraria rigidula is new to Montenegro. The lichen mycota is compared with similar localities in Italy and Switzerland.The species composition in Livari is most similar to the Montieri site in Tuscany.